2020
DOI: 10.1186/s12245-020-00298-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomised crossover comparison of two endotracheal tube introducers: the FROVA and the Flexible Tip Bougie for GlideScope intubation of a difficult airway manikin by infrequent intubators

Abstract: Background: This unblinded randomised crossover study compares two endotracheal tube introducers (ETIs): the FROVA and the "Flexible Tip Bougie" (FTB), in an airway manikin mimicking difficult intubation with a percentage of glottic opening view of 30%. Participants were Emergency Medicine and Anaesthesia trainees with recent experience of less than twenty patient intubations. The primary outcome was time to intubation, further divided into time taken to pass the ETI and time to railroad the endotracheal tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…There was no significant difference in the first attempt success rate between two groups. Alternative techniques to aid tube delivery with videolaryngoscopes have been described including stylets [22] and fibreoptic assisted videolaryngoscopy [23]. Despite the difference in bougie impingement, we were not able to demonstrate any statistically significant difference in incidence or severity of postoperative sore throat between the two groups.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…There was no significant difference in the first attempt success rate between two groups. Alternative techniques to aid tube delivery with videolaryngoscopes have been described including stylets [22] and fibreoptic assisted videolaryngoscopy [23]. Despite the difference in bougie impingement, we were not able to demonstrate any statistically significant difference in incidence or severity of postoperative sore throat between the two groups.…”
Section: Discussioncontrasting
confidence: 62%
“…We are not aware of any previous comparable clinical trials using flexible tip bougies. However, a significantly reduced anterior tracheal wall impingement, reduced number of optimisation manoeuvres and shorter intubation time has been observed in manikin studies using a flexible tip bougie when compared with a standard bougie [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…10 Another study conducted by Cormack et al obtained results indicating that total intubation time was significantly shorter with the Flexible Tip Bougie (37.5 s) compared to the Frova Intubating Introducer (63.0 s). 11 Additionally, the results from Evrin et al also showed that intubation time was significantly faster with the Flexible Tip Bougie (29.0 s) than a standard bougie (38.0 s). 14 Again, the intubation time with the Flexible Tip Bougie (37.0 s) was significantly shorter than with a standard bougie (55.0 s) in a study by Frass et al 9 Brunckhorst et al also concluded that the intubation time was significantly faster with the Flexible Tip Bougie (77.2 s) as compared to the Frova Intubating Introducer (142.2 s).…”
Section: Resultsmentioning
confidence: 98%
“…The results remain in line with several previous studies which were in favour of the Flexible Tip Bougie compared to others in term of ease of use. [7][8][9][10][11]14 According to feedback from the participants, the Flexible Tip Bougie is easier to use because of its anterior curve of body and the flexible tip that can be directed both anteriorly and posteriorly. In the scenario of difficult airway, it is important to select the easiest to use and most familiar bougie to facilitate successful intubation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation